2021
DOI: 10.3390/jcm10215205
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Sydrome and Decrease in Health-Related Quality of Life in Kidney Transplant Recipients after SARS-COV-2 Infection—A Cohort Longitudinal Study from the North of Poland

Abstract: Introduction: Patients after SARS-CoV-2 infection frequently face “Post-COVID-19 Syndrome”, defined by symptoms that develop during or after COVID-19, continue for more than 12 weeks, and are not explained by an alternative diagnosis. We aimed to evaluate the presence of post-COVID-19 syndrome and its predictors in kidney transplant recipients (KTR) 6 months after the disease. Materials and Methods: A total of 67 KTR (38 m) with a mean age of 53.6 ± 14 years, 7.3 ± 6.4 years post-transplant were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 30 publications
5
27
0
Order By: Relevance
“…The most common symptom in our patients was weight or muscle loss (53%), consequences that have seldom been explored in other studies. As in other studies, extreme fatigue and weakness was frequently observed: 32% in our dialysis patients versus 61% in the Gdansk hemodialysis population [ 6 ] or 43% in the Gdansk transplanted population [ 5 ], and 39% to 73% in a systematic review [ 1 ]. Breathlessness is often recorded in the general population (39–74%) [ 1 ] but is less common in dialysis patients: 15% in our study and 34% in the Gdansk study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The most common symptom in our patients was weight or muscle loss (53%), consequences that have seldom been explored in other studies. As in other studies, extreme fatigue and weakness was frequently observed: 32% in our dialysis patients versus 61% in the Gdansk hemodialysis population [ 6 ] or 43% in the Gdansk transplanted population [ 5 ], and 39% to 73% in a systematic review [ 1 ]. Breathlessness is often recorded in the general population (39–74%) [ 1 ] but is less common in dialysis patients: 15% in our study and 34% in the Gdansk study.…”
Section: Discussionsupporting
confidence: 66%
“…In this study, diabetes and estimated glomerular filtration rate predicted the development of post–COVID-19 clinical complications. In another study of 67 kidney transplant patients, post-COVID syndrome was diagnosed in 70% at 6 months, and 26% reported at least 3 persistent symptoms [ 5 ]. In this study, persistent symptoms were more frequent in older patients and in those with more comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a meta-analysis of 15,244 hospitalized and 9,011 outpatients with COVID-19, it has been calculated that at least one persistent disease symptom persists 90 days after the onset of the disease in more than 45% of patients [54]. Studies in patients treated with renal replacement therapy are sparse in this respect, but indicate that six months after the disease, the percentage of patients with Post-Covid syndrome may affect as much as 81% of HD patients and 71% of KTR [55,56].…”
Section: Serious Sequelae Of the Diseasementioning
confidence: 99%
“…What distinguishes patients undergoing renal replacement therapy from the general population is the long-lasting feeling of heart palpitations in HD patients, as well as increased hair loss in KTR. Importantly, persistent symptoms significantly translate into a deteriorating quality of life [55,56]. However, one should approach the published reports on the Post-Covid syndrome with some caution.…”
Section: Serious Sequelae Of the Diseasementioning
confidence: 99%